2005
DOI: 10.1109/tuffc.2005.1503998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contrast agent infusion rates on thresholds for tissue damage produced by single exposures of high-intensity ultrasound

Abstract: Stabilized microbubble ultrasound contrast agents (UCA) have potential to aid tissue ablation during ultrasound surgery by enhancing both cavitational and thermal damage mechanisms. Previously, we showed UCA infused at a rate of 1 L/kg/min prior to ultrasound exposure could reduce the total energy required to produce tissue damage by up to two orders of magnitude. In this paper, we evaluate thresholds for macroscopic tissue damage with UCA infusion rates (IR) of 0.1, 0.3, 1, 3, and 10 L/kg/min to determine IR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Ultrasound contrast agents, such as preformed microbubbles, amplify focal heating during sonication and have been used to reduce the time-averaged power needed during transcranial FUS ablation. 79 In a study on rabbits, McDannold et al 60 demonstrated that the administration of a microbubble-based ultrasound contrast agent reduced the acoustic power needed to induce lesions to less than one-tenth of what is required to produce thermal lesions without the contrast agents.…”
Section: Tumor Thermocoagulationmentioning
confidence: 99%
“…Ultrasound contrast agents, such as preformed microbubbles, amplify focal heating during sonication and have been used to reduce the time-averaged power needed during transcranial FUS ablation. 79 In a study on rabbits, McDannold et al 60 demonstrated that the administration of a microbubble-based ultrasound contrast agent reduced the acoustic power needed to induce lesions to less than one-tenth of what is required to produce thermal lesions without the contrast agents.…”
Section: Tumor Thermocoagulationmentioning
confidence: 99%
“…They showed that these MBs significantly lowered the threshold for tissue damage: Both the required intensity and exposure duration were reduced when MBs were present. They also evaluated the threshold for macroscopic tissue damage with MB infusion rates (IR) to determine is the level that was effective for HIFU ablation in the kidneys of adult female dogs (Tran et al 2005). In this study, canine kidneys were exposed to HIFU with 1.44-MHz tone bursts.…”
Section: Effects In the Kidneymentioning
confidence: 99%
“…One method of improving the safety profile of cavitation is with the administration of microbubbles, which are commonly used as an ultrasound imaging contrast agent. In this instance, lower power ultrasound can be delivered to achieve similar cavitation effects, because one is not relying on ultrasound-induced nucleation of gas bubbles within the tissue 26-30 .…”
Section: Mechanismsmentioning
confidence: 99%